Perancangan Rak Tempe Ergonomis untuk Meningkatkan Efisiensi Pekerja di CV. Mulya Tempe - Farah Zahila; Erni Puspanantasari Putri (Jurnal Serambi Engineering, 2024)
CV. Mulya Tempe operates in the food sector, namely leaf tempeh, plastic tempeh, mendoan tempeh and round tempeh. The traditional process of making tempeh leaves takes approximately 80 hours or 3 days until the tempeh product is perfectly cooked. In the molding stage, the soybeans are compacted on a rack by hitting them using wooden tools by two workers. This compaction process was repeated 10 times repeatedly. In addition, at the fermentation stage, additional load is provided by stacking red bricks on top of the compacted soybeans. In the molding or compaction stage, the worker's position is standing and bending. Five Mulya Tempe workers experienced complaints about the neck, elbows, arms, back, waist and calves because the shelves owned by Mulya Tempe did not match the anthropometric measurementsof the workers' bodies. The results of calculating work attitudes using the REBA method get scores of 10 and 11, where the scores fall into the high and very high categories, which requires improvement in work attitudes. Where the tempeh fermentation rack was redesigned by carrying out calculations using anthropometric data, percentiles, data adequacy tests and data uniformity tests.